Developing a statewide protocol to ensure patients with suspected emergent large vessel occlusion are directly triaged in the field to a comprehensive stroke center: how we did it. (3rd March 2016) - Jayaraman, Mahesh V; Iqbal, Arshad; Silver, Brian; Siket, Matthew S; Amedee, Caryn; McTaggart, Ryan A; Paolucci, Gino; Rhodes, Jason; Potvin, John; Tucker, Megan; Alexander-Scott, Nicole
Abstract : We describe the process by which we developed a statewide field destination protocol to transport patients with suspected emergent large vessel occlusion to a comprehensive stroke center.